Prediction of Islamic Banking Bankruptcy in Indonesia: Comparative Study of Altman Z-Score and Springate Models - Nata, Shafitra -; Chairunnisa, Rizka; Arshed, Noman (Universitas Islam Negeri Raden Intan Lampung, 2020)
Aim of this research is to calculate, measure, analyze, and evaluate predictions of potential bankruptcy of Islamic banking using the modified Altman Z-Score and Springate models and identify differences in the predicted results. This research uses descriptive quantitative analysis. Model analysis used is the Modified Altman Z-Score and Springate models. The research object used is 12 Islamic banks in Indonesia 2013-2019 and data collection includes literature study and observation.Modified Altman Z-Score model predicts that 1.19% of Islamic banking is in gray area and 98.81% is in a non-bankrupt position. Meanwhile, the Springate model predicts 38.10% of Islamic banking is in a bankrupt position and 61.90% is in a non-bankrupt position. This research only analyzes and compares the prediction results of the potential bankruptcy of Islamic banking with the modified Altman Z-Score and Springate models.This research can be used as an evaluation material for Islamic Banking in Indonesia in the face of potential bankruptcy so that companies can immediately improve their management and company performance.